Microbiological analysis of dental casts stored long-term - Gallão, Simone; Pizzolitto, Antonio Carlos [UNESP]; Santos-Pinto, Lourdes [UNESP]; Santos-Pinto, Ary dos [UNESP]; Faltin Junior, Kurt [UNESP]; Martins, Lídia Parsekian [UNESP] (Elsevier, 2013)
Background: The aim of this study was to evaluate the presence of bacteria and fungi on dental plaster casts stored long-term. Methods: Forty-four pairs of dental casts stored since 1980e1981 were used. The material for microbiological analysis was collected with a swab and cultivated in brain-heart infusion cultures and Sabouraud dextrose broth for subsequent plating and colony identification. Results: Bacterial growth such as coagulase-negative Staphylococcus, Micrococcus sp., Bacillus sp., and nonfermenting gram-negative bacillus were present in 25% of the samples, whereas fungal growth such as Cladophialophora sp., Trichosporon beigelii, Aspergillus flavus, and Aureobasidium pullulans were found in 5.7%. Conclusions: There was growth of opportunistic bacteria and fungi, posing no risk to healthy people
Keywords: Bacteria; Fungi; Plaster cast